Rod and Cone Coupling Modulates Photopic ERG Responses in the Mouse Retina - Li, Yichao; Cohen, Ethan D.; Qian, Haohua (Frontiers in Cellular Neuroscience, 2020)
Light adaptation changes both the sensitivity and maximum amplitude (Rmax) of the mouse photopic electroretinogram (ERG) b-wave. The light adaptation enhancement factor (LAEF), defined as the ratio of Rmax after 15 min light adaptation to Rmax recorded at the onset of an adapting light, was 2.64 ± 0.29 for wildtype mice (WT), but was significantly reduced (1.06 ± 0.04) for connexin 36 knock out (Cx36KO) mice, which lacks electrical coupling between photoreceptors. Wild type mice, intraocularly injected with meclofenamic acid (MFA), a gap junction blocker, also showed a significantly reduced LAEF. Degeneration of rod photoreceptors significantly alters the effects of light adaptation on photopic ERG response. Rd10 mice at P21, with large portions of their rod photoreceptors present in the retina, exhibited a similar b-wave enhancement as wildtype controls, with LAEF of 2.55 ± 0.19. However, by P31with most of their rod photoreceptors degenerated, rd10 mice had a much reduced b-wave enhancement during light-adaptation (LAEF of 1.54 ± 0.12). Flicker ERG responses showed a higher temporal amplitude in mesopic conditions by signals through rod-cone coupling pathways. In conclusion, our study provides a novel method to noninvasively measure the dynamics and modulation by light adaptation for rod-cone gap junctional coupling in intact eyes.